PENGARUH EDUKASI MELALUI MEDIA LEAFLET TERHADAP PENGETAHUAN DAN SIKAP SISWA SMAN 14 BOMBANA TENTANG COVID 19 - Enindelastri Enindelastri; La Ode Muhammad Sety; Adius Kusnan (NHM PRESS, 2021)
Knowledge about Covid 19 is defined as the result of knowing about the disease, understanding the disease, how to prevent it, treat it and complications. The purpose of this study was to determine the effect of knowledge, attitudes and behavior through leaflets and audiovisual media on students of SMAN 14 Bombana in the islands of Masaloka Raya, Bombana Regency. This type of research is quasi-experimental with a non-equivalent control group design with pretest and posttest. The study was conducted by dividing the respondents into 2 groups, namely 1) the experimental group was given leaflet media education and 2) the control group was given audiovisual media education. The population of the study was 146 people, a sample of 106 people, 53 experimental samples and 53 control samples. The results of the normality test obtained that the data was not normally distributed so that the Wilcoxon test analysis was used. The results showed that leaflets and audiovisual media were able to increase the level of knowledge (Asymp.sig (2-tailed) = 0.007 and 0.000), attitudes (Asymp.sig (2-tailed) = 0.003 and 0.005), both before and after education. There are differences in the knowledge, attitudes and behavior of the leaflet and audiovisual media groups, the knowledge of Asymp sig (2-tailed) = 0.015, the attitude of Asymp sig (2-tailed) = 0.000. the influence of the level of knowledge of attitudes and behavior of SMAN 14 Bombana students about Covid 19.